Perceptions Toward the Use of Digital Learning Resources Versus Traditional Textbooks in Studying Core Accounting Subjects Among Accountancy Students of Cavite State University Main Campus, S.Y. 2025–2026 - Ortega, Jewel Joyce B.; Sustrina, MariaIsolde R.; Ilagan, Mary Grace A.; Desepida, Maria Cristina L.; Bigalbal, Elizabeth D.; Corpuz, Jaysi T.; Trangia, Leonil P.; Soriano, Meiri Gleidelle A.; Salvador, Kristine Nicole T.; Laguardia, Izzel Mae F.; de Mesa, Mayrine Angel S.; Naines, Ameeryl Precious D. Naines; Aguilar, Dolores L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
A cross-sectional study was conducted in a state university in the Province of Cavite which covered the academic year 2025-2026 and explored the perceptions of accountancy students toward the use of digital learning materials as against traditional textbooks in studying core accounting subjects. Specifically, it aims to characterize the participants in terms of age, gender, year level, and monthly family income, investigate how often and in what situations accountancy students use digital and printed textbooks, examine the advantages and disadvantages of using both materials in learningaccounting core subjects, and recognize preferences. The research employed both quantitative and qualitative research with emphasis on the students’ experiences and perceptions. The entire population of 242 students enrolled under the accountancy program were included in the data collection applying in-depth and key informant interviews and focus group discussions, per year level. Responses were decoded manually following the steps of thematic analysis of Braun and Clark (2006). The findings revealed that printed textbooks remain as the main learning resources for students, with most indicating that they “often” use them while studying as a foundational resource. In contrast, digital materials are “often” utilized to augment the learning process. Further, the demographic profile of the participants is not a factor on the perceptions of students towards both digital and traditional learning materials; rather, the context of use is the main driver of their preference between digital and traditional learning materials. Students alternately use both printed and digital materials, allowing one to supplement the gaps of the other.